Design and Validation of a Portable Wireless Data Acquisition System for Measuring Human Joint Angles in Medical Applications - Xu, Weiyang (Curtin University, 2018)
A prototype sensor system to capture and measure human joint movements in medical applications was developed. An algorithm that uses measurements from two IMU sensors to estimate the angle of one human joint was developed. Custom-made hardware and software were developed. Validation results showed 0.67° maximum error in static condition, 1.56° maximum RMSE for dynamic measurements and 2.5° average error during fast movements’ tests. The prototype has been successfully used by medical teams.